VERTICAL DISTRIBUTION AND DENSITY OF CORAL FUNGIIDAE ON MALALAYANG WATERS - Mampuk, Friska; Tioho, Hanny; Kusen, Janny D. (JURNAL PESISIR DAN LAUT TROPIS, 2013)
Fungiidae known as a solitaire coral, attachment and also free living and has capability of individual move for migrate.  Their mobility allows them to expand the area, providing a hard substrate for coral recruitment and shelter for other invertebrates.  The objective of this study was to examine the density and distribution of fungiid corals in Malalayang waters. The data were collected from September to December 2012 at four different areas.  The results of this study showed that the highest density of fungiid corals were occurred on the front reef study site and mostly by Fungia danai (0,62 ind/m2), compared with other species such as Herpolitha limax (0,25 ind/m2), F. paumotensis (0,19 ind/m2), F. fungites (0,18 ind/m2), F. granulosa (0,18 ind/m2) and with an aggregated pattern of distribution.   Fungiid corals found in this study were mostly relatively more on the reef flat compared to the reef slope.